2020
DOI: 10.3390/nu12030596
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Orally Dosed Levagen+™ (palmitoylethanolamide) on Exercise Recovery in Healthy Males—A Double-Blind, Randomized, Placebo-Controlled Study

Abstract: The aim of this study was to evaluate the effect of palmitoylethanolamide (PEA), a cannabimimetic compound and lipid messenger, on recovery from muscle damaging exercise. Twenty-eight healthy young male participants attended the laboratory four times on subsequent days. In the first visit, baseline characteristics were recorded before participants were randomized to consume either liquid PEA (167.5 mg Levagen+ with 832.5 mg maltodextrin) or a matched placebo (1 g maltodextrin) drink. Leg press exercise consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The results are in line with PEA’s ability to reduce muscle protein breakdown as shown by a significant increase in protein kinase B (Akt) phosphorylation, a kinase known to induce protein synthesis [ 188 ], and the ability to clear myoglobin from the circulation [ 31 ]. The fall in lactate levels is not yet fully understood but reflects decreased lactate production and/or increased uptake into surrounding tissues.…”
Section: Pea and Exercise Recoverysupporting
confidence: 53%
See 2 more Smart Citations
“…The results are in line with PEA’s ability to reduce muscle protein breakdown as shown by a significant increase in protein kinase B (Akt) phosphorylation, a kinase known to induce protein synthesis [ 188 ], and the ability to clear myoglobin from the circulation [ 31 ]. The fall in lactate levels is not yet fully understood but reflects decreased lactate production and/or increased uptake into surrounding tissues.…”
Section: Pea and Exercise Recoverysupporting
confidence: 53%
“…PEA’s application to an exercising population and potential for muscle recovery is not well understood. To date, only one clinical trial has assessed the impact of PEA on recovery from muscle-damaging exercise [ 31 ]. This study found that the group consuming 176.5 mg of a high-bioavailability form of PEA (containing NLT 158 mg PEA) in liquid form had significantly lower myoglobin and blood lactate levels than the placebo group.…”
Section: Pea and Exercise Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…However, both parameters decreased with increasing CT supplementation in exercised rats, which suggests a dose-response of these effects. Lactate production has been linked to insufficient muscle oxygenation and, consequently, results from fatigue and muscle soreness [ 40 , 41 ]. As outlined by other researchers, and in agreement with the present, L-carnitine has been shown to reduce lactate production and improve exercise performance [ 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, exercise interventions were shown to modulate PEA, a ligand of GPR55, in the muscle of women with chronic neck shoulder pain [58]. In a randomized controlled trial, oral doses of PEA improved several markers associated with muscle recovery after exercise [59]. These studies support the idea that exercise increases a GPR55 agonist, which could potentially link back exercise anxiolytic activity to eCBome-mediated activation of GPR55.…”
Section: Exercise and Endocannabinoidsmentioning
confidence: 75%